SPEECH RECOGNITION USING SOFT COMPUTING - Pandey, Digesh (International journal of advanced research in computer science, 2022)
The work of speech affirmation is one of the entrancing field with respect to speech signal taking care of. Achieving accuracy and strength is a very problematic limit to various regular components. Reformist work and reviews in the speech recognition application has been gotten using Soft Computing, as one of the system to further develop the affirmation exactness’s. This research paper reviews the various thoughts of Soft Computing procedure and its applications to speech signal taking care of an area. Since the possibility of speech signal is questionable, it doesn't deal with consistency at immaculate stretches. To deal with this irregularity and weaknesses, various researchers have proposed soft computing is one of the better technique to separate the speech signals. This research paper presents the composing work open related to speech recognition using Soft computing methodology.